2011
DOI: 10.1111/j.1600-0501.2011.02355.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for interfacial biochemical bonding in osseointegrated titanium implants

Abstract: The present study has provided quantitative evidence for biochemical bond theory of osseointegration of implants with bioactive surface oxide chemistry, ATiO(x) B. The theory of biochemical bonds may provide a scientific rationale pertinent to recent emerging trends and technologies for surface chemistry modifications of implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Different NC bonds led to a peak broadening between 397 and 402 eV and could not be distinguished from each other. Hence, this broad peak was formally divided into three parts CN (1) , CN (2) , and CNOH: CN (1) and CN (2) for miscellaneous covalent CN bonds such as CNH 2 , CN, CN, CNC, OCNH 2 , and OCNHR. After 360 storage days the intensity of the total peak is clearly reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different NC bonds led to a peak broadening between 397 and 402 eV and could not be distinguished from each other. Hence, this broad peak was formally divided into three parts CN (1) , CN (2) , and CNOH: CN (1) and CN (2) for miscellaneous covalent CN bonds such as CNH 2 , CN, CN, CNC, OCNH 2 , and OCNHR. After 360 storage days the intensity of the total peak is clearly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Note (a) the decreasing primary amino groups (CF 3 bonds near 297.7 eV) and the increasing acid amide bonds (CO, NCO at 288.0 ± 0.3 eV) and carboxylic acid bonds (COOH at 289.2 ± 0.2 eV). The N 1s peak (b) is formally fitted by different peaks which are marked by CN(1) , CN(2) , and CNOH. CN(1) , CN(2) for miscellaneous covalent CN bonds: CNH 2 , CN, CN, CNC, OCNH 2 , OCNHR after deposition and storage in ambient air for 360 d.…”
mentioning
confidence: 99%
“…In removal torque testing, it was shown that the fracture phase at the bone interface occurred mainly within the periimplant bone for the Mg-doped implant surface [21]. Sul et al [22] suggested that the modification of the titanium oxide with magnesium results in a so-called ''biochemical bonding'' of the surfaces with bone, probably as a result of the change in the surface polarity (from negative to positive) and an improved chemical interaction between the local environment and the altered surface. In a previous rabbit study, the present authors observed significantly higher removal torque values for mesoporous implant surfaces loaded with Mg ions compared with non-loaded controls, after 3 weeks of healing [11].…”
Section: Introductionmentioning
confidence: 98%
“…With the help of atom probe tomography, Karlsson et al have recently determined that bone 5 bonds chemically to Ti implant through direct contact between calcium atoms and titanium oxide surface after osseointegration 18 . Nevertheless, since the strength at the basic level of biochemical bonding is inherently weak, a more powerful mechanism is required to achieve a higher strength at the functional level [19][20] . It has been suggested that synergistic role of surface chemistry and micro-topography would be more beneficial for the achievement of higher bone/implant stability [20][21] .…”
Section: Introductionmentioning
confidence: 99%